Broadband Power Amplifier Design via Fictitious Matching - Kilinc, Sedat; Siddik Yarman, B.; Özoguz, Serdar (Institute of Electrical and Electronics Engineers (IEEE), 2022)
In this paper, we introduce a new matching concept, so called Fictitious Matching (FM), which may be defined between the artificially generated non-Foster passive immittances, namely KGF and KLF, over a lossless two-port or equivalently equalizer E. These immittances may not necessarily belong to physical devices, rather, they are fabricated like a source-pull or load-pull impedances to maximize the gain, the output power, the efficiency, and to minimize the output harmonics of a nonlinear-active device. In FM problems, E is constructed to optimize the power transfer from KGF to KLF in the passband. In this regard, E is described by means of its back end driving point input immittance K(λ) in Darlington sense, and it is determined as the outcome of the optimization process, where the complex variable λ=Σ+jΩ refers to Richards variable. Synthesis of K(λ) results in E, consists of commensurate transmission lines. It is demonstrated that the new concept of FM can be utilized to build broadband power amplifiers. In this work, solving FM problem successively, the input and the output matching networks of a power amplifier are designed over 500 MHz-3 GHz with the average gain of 11.5dB, the output power of 40.5dBm, and the average drain efficiency of 61.7%. The Power Amplifier was manufactured with microstrip lines using Wolfspeed’s CGH40010F GaN transistor. IEEE
Keywords: III-V semiconductors; Broadband Matching; Load pull; Efficiency; Microstrip; Natural frequencies; Microstrip-line; Commensurate transmission line; Frequency modulation; Richard variable; Source pull impedance; Microstrip Lines; Richards Synthesis; Impedance matchings; Impedance matching; Real Frequency Techniques; Transmission-line; Real frequency technique; Source Pull Impedance; Broadband amplifiers; Passband; Power amplifiers; Load pull impedance; Pass bands; Impedance; Gallium nitride; GaN Power Amplifiers; Broad band matching; Commensurate Transmission Lines; Electric lines; Micro-strips; Parametric approach; Energy transfer; Richards Variable; Microstrip lines; Power transmission lines; Parametric Approach; Richard synthesis; GaN power amplifier; Source-pull; Load Pull Impedance